Pathogenic and genetic variability among Colletotrichum gloeosporioides isolates from different yam hosts in the agroecological zones in Nigeria - Abang, Mathew M.; Asiedu, Robert; Hoffmann, P.; Wolf, G.A.; Mignouna, Hodeba D.; Winter, S. (Wiley, 2006)
Anthracnose, caused by Colletotrichum gloeosporioides Penz., is the most severe foliar disease of water yam (Dioscorea alata) worldwide. Population genetic analyses can yield useful insights into the evolutionary potential of C. gloeosporioides and thus lead to the development of appropriate disease management strategies. The genetic structure of C. gloeosporioides populations from yam and non-yam hosts in three agroecological zones of Nigeria was investigated. Microsatellite-primed polymerase chain reaction (MP-PCR), virulence phenotyping using five putative D. alata differentials, cross-inoculation tests, and the presence/absence of a Glomerella teleomorph in yam fields were used to infer the evolutionary potential of C. gloeosporioides on yam. We observed high genotypic diversity (GD = 0.99 to 1.00) for populations from all hosts and agroecological zones, with multiple pathogen genotypes in individual anthracnose lesions. Genetic differentiation was low among pathogen populations from different hosts (GST = 0.10, θ = 0.034), and agroecological zones (GST = 0.04, θ = 0.018), indicating limited host differentiation and significant gene flow. No evidence was found for the existence of C. gloeosporioides f. sp. alatae reported in previous studies. The fungus was recovered from several non-yam host species commonly found in yam fields but non-yam isolates caused only mild to moderate symptoms on yam. Eighteen C. gloeosporioides virulence phenotypes were identified among 217 isolates but there was a weak correlation (r = 0.02, P = 0.40) between virulence phenotype and MP-PCR haplotype. Consistent with the above findings, we observed for the first time the Glomerella teleomorph on anthracnose-infected yam plants in Nigeria, indicating that sexual recombination might play an important role in anthracnose epidemics on yam. The implications of these findings for C. gloeosporioides evolutionary potential and anthracnose resistance breeding are discussed.